Frequency and related factors of alexithymia in patients with fibromyalgia treated at a public hospital in Lima, Peru. - Nestares Luna, Kim Leslie (2021)
Objective: To determine the frequency of alexithymia and associated factors in patients with fibromyalgia, and the relationship between alexithymia with functional capacity, pain intensity, depression and general variables (age, sex, time of illness, degree of instruction, and years of study) in fibromyalgia. Material and methods: Descriptive cross-sectional study of patients with fibromyalgia from the Rheumatology service of a  public hospital in Lima, Perú. A sociodemographic record, TAS-20, MD-HAQ and CES-D were applied. Results. Of the 126 patients with fibromyalgia, 60 had alexithymia (47.62%); 24 alexithymic patients had depression (40 %), and 39 had functional disability (65 %). In the bivariate analysis, alexithymia was significantly related to greater comorbidity, less education, greater pain intensity, greater fatigue and more reported symptoms. In the multivariate analysis, years of study (£ 11 years) were the only factor related to alexithymia (TAS-20) (p=0.010, OR: 2.589 [1.249 – 5.365]). Conclusions: This study shows a considerable frequency of alexithymia in fibromyalgia patients and, in the multivariate analysis,  the finding is significantly related to a lower number of years of study.